2018
DOI: 10.1017/s2047102518000092
|View full text |Cite
|
Sign up to set email alerts
|

Legal and Policy Pathways of Climate Change Adaptation: Comparative Analysis of the Adaptation Practices in the United States, Australia and China

Abstract: To successfully respond to climate change impacts, it is imperative that governments structure adaptation laws and policies around their country’s existing legal framework. The United States (US), China, and Australia have all made adaptation attempts through legislative, executive, and judicial action. However, because the systems of law and governance of the three countries differ, the ways in which adaptation issues are managed vary. State and local adaptation planning functions as the leading adaptation pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…For increasing the adaptive capacity, it becomes especially crucial to jointly develop strategies for water systems with involved actors at a regional scale to develop complementary and parallel strategies for which investments of other actors are (also) needed. Also designing legal and policy pathways toward adaption, for example, for enabling cooperation, could become part of this participatory and regionally embedded exercise (He, 2018). For increasing the transformative capacity, it becomes crucial to organize dialogues with stakeholders within regions to develop a future vision and to discuss possible win‐wins but also unavoidable clashes of stakes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For increasing the adaptive capacity, it becomes especially crucial to jointly develop strategies for water systems with involved actors at a regional scale to develop complementary and parallel strategies for which investments of other actors are (also) needed. Also designing legal and policy pathways toward adaption, for example, for enabling cooperation, could become part of this participatory and regionally embedded exercise (He, 2018). For increasing the transformative capacity, it becomes crucial to organize dialogues with stakeholders within regions to develop a future vision and to discuss possible win‐wins but also unavoidable clashes of stakes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…As the Chinese government adjusts the problem definition of climate change and refines its climate policy goals, it is also updating its strategies on climate change. Climate adaptation and risk management was historically a much lower priority on the domestic policy agenda in China compared to climate mitigation [48][49][50]. In recent years, Chinese scientists have launched several systematic studies on climate risk assessment and management.…”
Section: Learning To Elevate Adaptation Action Onto An Equal Footing ...mentioning
confidence: 99%
“…Of the 130 articles identified systematically, 99 (76% of the total dataset) focus on Global North jurisdictions (either in an in‐depth analysis or as part of a comparative project), 26 (20% of the total dataset) have an international focus or cover jurisdictions in both North and South. Only five of the identified journal articles have a clear focus on litigation or litigation‐related issues in the Global South (He, ; Humby, ; Nyinevi, ; Ugochukwu, ; Williams, ) (Figure ). Other contributions to the literature on climate litigation in Global South countries can be found in edited books (Lord, Goldberg, Rajamani, & Brunnée, ) and as book chapters (Lin, ), but a first comprehensive study focused on Global South climate litigation is yet to be published.…”
Section: Overview Of the Literature On Climate Change Litigationmentioning
confidence: 99%
“…Mindful of such considerations, we sought to categorize the papers according to the type of different policy responses involved in the litigation to address climate change. We found that most papers were concerned with litigation to address mitigation (113 papers referred to mitigation-relevant litigation), 50 referred to adaptation-relevant litigation (e.g., He, 2018;Markell & Ruhl, 2010;O'Donnell, 2016;Peel, Godden, & Keenan, 2012;Preston, 2016b;Wilensky, 2015), and 20 papers referred to litigation concerned with addressing climate-related loss and damage (e.g., Hinteregger, 2017;Marjanac & Patton, 2018;Mayer 2014;Preston, 2016b;Spitzer & Burtscher, 2017). The 49 papers addressed both mitigation, adaptation and/or loss and damage (Figure 2).…”
Section: Increased Interest and Its Patternmentioning
confidence: 99%